MEWIRAUSAHAKAN BIROKRASI - Hakim, Lukmanul (AMONG MAKARTI, 2013)
Abstrak A context about bureaucracy of entrepreneurship prominently become a discussion of Indonesian bureaucracy during various crisis that wave government base and economic. The fairness of information and democratic mainstream that coloured "reformation movement" has opened our taboo bureaucracy from the two sides. One side is a certainly of those information mainsleam influenced by global issues factor and technological progress, while, on the other side a political change has support to community to stale the value of government bureaucracy s activities. Thus. our bureaucracy's face is obviously pleasant, even with public eyes as the the fact that our bureaucracy is gelling muss and then (hey can not maximized their works, effelively and efficiently. A while, the modern life demands, heauracracy's role as "mediaty agent" for government and community in the frame of civil society. Our beauracracy condition is as above desribed is the real description surrounding us, yet. It is signifk'anliy has a role in modern social especially in society's life. However, developing from that situation emerge idea about entrepreneiirship heauracracy in Indonesia. The discussion then. impress to cut off the line, from the slow beauracracy to heasman one, from the way of "a hone of contention" to be a professional one. Key word : beauracracy, enterpreunership, enlerpreunership beauracracy